2014
DOI: 10.5009/gnl13183
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Growth in Korean Children with Crohn’s Disease: A Single-Center Study

Abstract: Background/AimsMalnutrition and growth retardation are important issues in treating pediatric Crohn’s disease (CD). Thus, we aimed to investigate the prevalence of various nutritional and growth parameters at the time of diagnosis in Korean children with CD.MethodsSeventy-one children (<18 years) were enrolled. We analyzed the Z-scores of height-for-age (HAZ), weight-for-height (WHZ), body mass index for age (BMIZ), bone mineral density for age (BMDZ), and the biochemical markers measured at the time of diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
5
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 33 publications
3
47
5
2
Order By: Relevance
“…Aghazadeh et al claimed that the intake of fluids, Mg and vitamin C is lower in IBD patients than in healthy people [19]. In a study conducted in 2014, Song et al reported that 72% of patients had micronutrients deficiency and about 10% of Crohn's disease patients were Mg deficient [7]. In our study, the mean serum level of Mg was significantly higher in the control group.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Aghazadeh et al claimed that the intake of fluids, Mg and vitamin C is lower in IBD patients than in healthy people [19]. In a study conducted in 2014, Song et al reported that 72% of patients had micronutrients deficiency and about 10% of Crohn's disease patients were Mg deficient [7]. In our study, the mean serum level of Mg was significantly higher in the control group.…”
Section: Discussionsupporting
confidence: 45%
“…In IBD cases, altered metabolism of minerals occurs mostly during flare-ups. Trace elements particularly copper (Cu) and zinc (Zn), may affect ability of mucosa in dealing with harmful effects of free radicals [7]. Zn is an antioxidant element essential for biological functions, homeostasis, metabolism, absorption and intracellular transport in enterocytes and hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other smaller cohorts found that zinc was deficient in up to 20% of patients, mainly in those with CD. Only 1 study reported a similar prevalence of 51% in newly diagnosed patients with CD. Zinc deficiency in patients with IBD may be attributed to low oral intake or poor absorption.…”
Section: Discussionmentioning
confidence: 97%
“…It was demonstrated in previous studies that iron deficiency is very common in patients with IBD, even under complete clinical remission, and iron sufficiency is often not sustainable following iron treatment due to ongoing inflammatory activity. 3,6 According to other studies, 14,16,[21][22][23] up to 90% of patients with IBD will have iron deficiency at presentation. This extremely high prevalence of iron deficiency at diagnosis is attributed to many known factors, such as decreased intake, gastrointestinal bleeding and iron loss, decreased absorption capacity, as well as chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%